COGNITIVE AND CULTURAL ASPECTS OF TRANSLATING EMOTIONALLY CHARGED PHRASEOLOGICAL UNITS FROM UZBEK INTO ENGLISH - Maktuba Makhamadalievna Khonsaidova (Modern American Journals, 2025)
This research work uses empirical analysis to investigate how cognitive and cultural aspects are linked to body-part metaphors interpreted in terms of the semantic aspects of translation of anthropocentric idioms in Uzbek and English languages. Drawing on Conceptual Metaphor Theory (Lakoff & Johnson, 1980) and Cultural Linguistics (Sharifian, 2017), it identifies metaphorical motives by referring to body parts, such as head, heart, brain or other parts as expressions of intellect in idiomatic approaches beyond the translation norms. Moreover, these analyses conduct a contrastive investigation using bilingual corpora (collection of passages in two languages with parallel interpretation) and emphasize some valuable idioms which carry deeply rooted cultural meanings in both languages. Meanwhile, this study analyses the importance of Anthropocentric idioms which mainly give cognitive insights based on human-related words and their semantic expression in translation between two languages. Conceptual metaphor theory is used as a guide to illustrate human based idioms which serve a significant framework to propose relevant translations between these languages through cultural patterns. It also provides some vital information about relationship between culture, language and cognition in terms of cognitive linguistics which could be determined as Ethnolinguistics. The study of cultural cognition is an integrated motion of the cognition and culture as they both relate to language which has multifunctional and parallel forms that constantly negotiated from our past generation to modern scholars. The most targeted objectives of the study are to define some emotional metaphors through the findings and to dive deeply understanding theoretical framework of the human-based idioms in both language usage. Employing Conceptual Metaphor Theory (Lakoff & Johnson, 1980) and Cultural Linguistics (Sharifian, 2017) as its theoretical frameworks, the paper explores how metaphor, emotion, and culture intersect in idiomatic meaning. Using a bilingual corpus of literary, oral, and audiovisual texts, we analyse patterns of metaphorization, emotional connotation, and pragmatic function to demonstrate how translators manage to preserve or adapt emotional nuance across linguistic boundaries. The results indicate that emotion-laden PUs often require interpretive, adaptive, and culturally sensitive rendering strategies to ensure emotional and pragmatic equivalence.
Keywords: Uzbek phraseology, rendering studies, emotional metaphor, cognitive linguistics, idiomatic expressions, societal equivalence, socio-pragmatic rendering, conceptual metaphor theory